2012
DOI: 10.1364/ol.37.004242
|View full text |Cite
|
Sign up to set email alerts
|

Beam quality degradation of a single-frequency Yb-doped photonic crystal fiber amplifier with low mode instability threshold power

Abstract: A current limit in power scaling of Yb-doped fiber amplifiers is the sudden onset of mode instabilities. We investigated this effect on a single-frequency Yb-doped photonic crystal fiber amplifier with a low mode instability threshold power. By measuring the overlap of the fiber output beam with the fundamental mode of an external cavity to be about 95%, we could exclude significant modal power transfer below a sharp power threshold. Furthermore, we directly measured the frequency resolved intensity noise spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 12 publications
2
28
1
3
Order By: Relevance
“…5b. It is also consistent with recent experimental findings [14], which showed that TMI in a Yb-doped PCF amplifier with a core diameter of 38 μm manifested itself as a chaotic oscillation of the beam intensity on a ms timescale. The results for the 1 kHz and 10 kHz cases display a similar behavior and are therefore not reproduced here.…”
Section: Numerical Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…5b. It is also consistent with recent experimental findings [14], which showed that TMI in a Yb-doped PCF amplifier with a core diameter of 38 μm manifested itself as a chaotic oscillation of the beam intensity on a ms timescale. The results for the 1 kHz and 10 kHz cases display a similar behavior and are therefore not reproduced here.…”
Section: Numerical Resultssupporting
confidence: 93%
“…We have shown how both quantum noise, RIN and amplitude modulation of the signal can act as a seed for TMI, and have shown by an approximate semi-analytical solution of our model that the upper limit on the TMI threshold is due to quantum noise. We also found that the threshold is quite insensitive to perturbations of the amount of signal accidentally launched into a HOM, which is consistent with the experimental results reported in [8,14]. Considering coupling between the LP 01 and LP 02 modes, we found that the coupling between these two Experimentally it has been found that various types of cooling of the fiber amplifier can lead to variations in the TMI threshold power [8].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…특히 비선형 현상은 본질적으로 광섬유의 출력이 증가함에 따라 더욱 심 각한 결과를 초래하게 된다는 점에서 현재까지도 이를 억제 하기 위한 다양한 방안들이 모색되고 있는 실정이다. 최근에 는 비선형 현상과 더불어 모드 불안정 현상 또한 광섬유 레 이저의 출력을 제한하는 요소가 될 수 있다고 보고되고 있는 데 [11,[40][41][42][43][44][45][46][47][48] , 이는 광신호의 평균 출력에 따라 출력 빔 모드 특 성이 심각하게 왜곡되는 현상으로, 특히 광섬유의 코어가 크 고 그 유효 개구수(Numerical Apeture)가 낮으며 상대적으로 펌프광 흡수율이 높은 막대형 이득 광섬유(Rod-Type Gain Fiber)에서 더욱 현저히 발생한다 [41][42][43][44][45][46][47] . [49][50][51][52][53][54][55][56][57] .…”
Section: 서 론unclassified